Exploring the Attitudes Towards Entrepreneurship in a Transforming Society. The Case of Poland - Osowska, Renata (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
This study is an analysis of the perception of entrepreneurship in Polish society across two decades, starting from 1990, which marked the end of communism. 129 articles have been analysed to identify the social value of entrepreneurship and later compared to public opinion surveys related to the beliefs about entrepreneurship. Findings reveal that although there was a substantial positive change in the value of entrepreneurship, the ambiguous beliefs about entrepreneurs created mixed attitudes towards entrepreneurship. The inclusion of the transitional period offers the opportunity to expand on the theoretical understanding of entrepreneurial development and to deliver effective support in developing the entrepreneurial society.